Penggunaan permainan make a match sebagai media pembelajaran mufrodat bahasa arab di MTSN kota Batu - Wahidah, Shofiyah Risalatul (Maliki Interdisciplinary Journal, 2025)
This study aims to examine the effectiveness of the Make a Match game as a learning medium for Arabic vocabulary (mufrodat) at MTsN Kota Batu. The research is motivated by the need for teaching methods that enhance students’ engagement, understanding, and motivation in learning Arabic vocabulary, which is often taught using rote memorization and lecture-based approaches. This qualitative descriptive study combines literature review and field observation. The innovation lies in the modified form of the Make a Match game, which no longer uses cards, but instead involves arranging scrambled letters into words, matching them with pictures (clippings), and constructing sentences based on those words. The findings show that this game successfully creates an enjoyable learning atmosphere, increases student participation, and strengthens contextual vocabulary mastery. Students are cognitively, socially, and physically engaged in each activity phase. The analysis based on active learning theory, constructivism, and multiple intelligences indicates that this approach aligns with modern educational principles that position students as active participants in learning. Therefore, this innovative version of Make a Match is a viable and effective alternative learning media for teaching Arabic vocabulary at the junior high school level. The findings show that this game successfully creates an enjoyable learning atmosphere, increases student participation, and strengthens contextual vocabulary mastery. Students are cognitively, socially, and physically engaged in each activity phase. The analysis based on active learning theory, constructivism, and multiple intelligences indicates that this approach aligns with modern educational principles that position students as active participants in learning. Therefore, this innovative version of Make a Match is a viable and effective alternative learning media for teaching Arabic vocabulary at the junior high school level.